Seeds of Zizyphus lotus: In Vivo Healing Properties of the Vegetable Oil. (8th June 2020) - Rais, C.; Slimani, C.; Benidir, M.; Elhanafi, L.; Zeouk, I.; Errachidi, F.; El Ghadraoui, L.; Louahlia, S.
Abstract : The present study has been undertaken in order to highlight the healing effect of Zizyphus lotus vegetable oil. The seeds of this plant contain an oil rate of 30%. The obtained results on the main elements composing the vegetable oil have shown that Zizyphus lotus vegetable oil has a low value of acidity index and it presents a not negligible degree of unsaturation. The value of the peroxide index of Zizyphus lotus vegetable oil is less than 10 which characterizes the most of conventional oils. Furthermore, the spectral analysis by gas chromatography has shown the presence of 53 majority and minority molecules. Thus, the evaluation of the healing activity of Z. lotus seed vegetable oil has demonstrated a highly significant effect against the negative control and silver sulfadiazine was used as conventional treatment for burns. Based on the obtained results, we can suggest that the oil extracted from the seeds of the studied plant could be used to cure wounds.